The Clinical and Steroid-Free Remission of Fecal Microbiota Transplantation to Patients with Ulcerative Colitis: A Meta-Analysis - Wai Ching Lam; Chen Zhao; Wen Juan Ma; Liang Yao (Gastroenterology Research and Practice)
Background and Purpose. Since the first case of fecal microbiota transplantation for the treatment of ulcerative colitis was described in the year 1989, there have been an increment of case reports, case series, cohort studies, and randomized controlled trials (RCTs). In this study, we were going to investigate general clinical remission, clinical response, and steroid-free remission of fecal microbiota transplantation. Methods. We searched Ovid Medline, Ovid EMBASE, and Cochrane Library, focusing prospective studies including randomized controlled trials and cohort studies. The outcomes were clinical remission, clinical response, steroid-free remission, and serious adverse events. We used RevMan 5.3 software for meta-analyses. Key Results. A total of 4 RCTs and 2 cohort studies (340 cases from 5 countries) were included. We found that FMT might be more effective than placebo on clinical remission (OR, 3.85 [2.21, 6.7]; P<0.001; I2=0%) and clinical response (OR, 2.75 [1.33, 5.67]; P=0.006; I2=49%), but no statistical difference on steroid-free remission (OR, 2.08 [0.41, 10.5]; P=0.37; I2=69%) and serious adverse events (OR, 2.0 [0.17, 22.97]; P=0.44; I2=0%). Conclusions and Inferences. Fecal microbiota transplantations were associated with significant clinical remission and response in ulcerative colitis patients while there was no significant difference found between FMT and placebo in steroid-free remission. Moreover, a common consensus on the route, volume, timing, preferred donor characteristics, and frequency of fecal administration is necessary to achieve remission.